Analiza Vebrovega estetskega doživljaja - Matjašič, Kristijan (Analiza (Ljubljana), 2025)
Every person experiences aesthetic perception throughout their existence. Everyday experiences of beauty and art are often taken for granted, and we rarely take the time to analyze them. France Veber, however, addressed exactly this in his extensive monograph Aesthetics. This not only applies to works of art but also to everyday objects, such as clothing and cars. We also speak of beauty in natural phenomena. However, these judgments are quite unreliable: it can happen that something seems beautiful to us at one moment, but after some time, it becomes insignificant. Or vice versa. For example, Van Gogh’s paintings were not very popular in his time, but over time, and especially now, he is considered one of the greatest painters of all time. Therefore, the concept of beauty is not only about aesthetic or artificial qualities but also fundamentally related to “human existence,” as Pirjevec writes. The article explores Veber’s aesthetic thought and discuss what aesthetic experiences and perceptions of beauty can be, as well as what underpins these experiences. Using Veber’s terminology, we will attempt to answer the question of what is perception and the intentionality of perception, while also reflecting on the possibility of inauthentic experiences.
Keywords: aesthetics; agentsko modeliranjeVeber; beauty; consciousness; doživljaji; estetika; experience; lepota; predstave; representation; Veber; zavest